THE STRUCTURE OF HYDROUS SPECIES IN NOMINALLY ANHYDROUS MINERALS: INFORMATION FROM POLARIZED IR SPECTROSCOPY - Libowitzky E.; Beran A. (My University, 2006)
Hydrogen is a major constituent in a wide variety of minerals in the Earth’s crust. Usually H is bonded to oxygen forming H 2 O molecules or OH − groups. In rare cases, H 3 O + , H 3 O 2− and H 5 O 2+ units are also formed. The occurrence of NH 4+ , CHx, etc. in minerals will not be considered here. Hydrogen occurs stoichiometrically in hydrous compounds such as hydrates (e.g., gypsum), (oxy)hydroxides (e.g., goethite), and in many rock-forming silicates (e.g., micas), as well as in nonstoichiometric major amounts in microporous minerals such as zeolites and clay minerals, which are of considerable economic and ecologic importance.